Implications of Allegations of Genocide in Contemporary International Relations - Ștefan, Gheorghe (Acta Universitatis Danubius. Relationes Internationales, 2022)
The issue of legal facts in international relations is a constant concern throughout the history of the relations of the states of the world from antiquity to the contemporary period. The idea of preventing them and punishing them properly, by holding them accountable both morally and especially politically or from the point of view of international criminal law, is a topic often approached by many contemporary experts today. Frequent military conflicts, revolutions, civil wars or riots, manifested over the centuries and especially in the twentieth and twenty-first centuries, have attracted the attention of the international public, which is increasingly interested in holding those responsible for violating the security climate accountable. the violation and violation of fundamental human rights and crimes against humanity.